Tinjauan Yuridis terhadap Penerapan Mediasi Online (Online Dispute Resolution) dalam Perkara Perceraian di Pengadilan Agama - Syahrani, Devy Fitri; Ramadhandiko, Difqa Alvi; Dorinda S, Gabriel; Kusuma, Nanda Putri Ananda; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2025)
Amid the wave of digitalization, the judicial system is required to adapt and innovate to provide faster, easier, and more efficient access to justice for the public. One rapidly evolving innovation is the implementation of Online Mediation (Online Dispute Resolution/ODR). According to Article 1 of the Supreme Court Regulation (PERMA) No. 1 of 2016, mediation is defined as a dispute resolution process conducted through negotiations between the disputing parties, assisted by a mediator to reach a mutual agreement. In the context of divorce cases, mediation is considered crucial as it may help reduce the high rate of divorce. The issuance of Supreme Court Regulation No. 3 of 2022 concerning Electronic Mediation further solidifies the status of online mediation as an official part of the dispute resolution mechanism within the court system. This research adopts a normative juridical approach and employs qualitative analysis through a case study of Divorce Petition No. 440/Pdt.G/2024/PA.Pct, relying primarily on secondary data sources.